Poverty Reduction and the World Bank : Progress in Operationalizing the WDR 2000/2001 - World Bank (Washington, DC, 2013)
Attacking persistent poverty in low- and middle-income countries is the greatest single challenge facing the global development community as the world moves forward into the 21st century. But despite progress during the past decade, the battle is far from won, and progress has been slower than had been hoped at the beginning of the 1990s. This report discusses how the Bank is responding to this challenge and translating the approach of the World Development Report 2000/2001 on poverty into practice. This edition of the annual Progress Report on Poverty Reduction consolidates the findings of two documents prepared by World Bank staff and presented to the institution's Executive Board in June 2001: a report, Poverty Reduction and the World Bank: Progress in Fiscal 2000 and 2001, and a paper, Attacking Poverty: Operationalizing the World Development Report 2000/2001 at the World Bank. Progress and prospects towards achieving development goals, encompass attention to trends in income poverty, and contain human capital achievements, but responsive to broader understanding, and sharper focus in strengthening intellectual underpinnings, and refining strategic directions, and country business environment. Country assistance strategies should be reoriented to improving poverty analysis, and monitoring results, within a framework to empower communities, increase opportunities, and strengthening security.